Geographical indications and trade: Firm-level evidence from the French cheese industry. (July 2021) - Duvaleix, Sabine; Emlinger, Charlotte; Gaigné, Carl; Latouche, Karine
Highlights: Investigation of the effect of GI on perceived quality, prices and trade margins. Use of firm-product data of to identify PDO trade flows of French cheeses and butters. PDO label benefits from a price premium and is perceived as a quality signal. The role of the demand effect for PDO varieties is confirmed. GI have a positive effect on market access to some markets (EU or with a similar GI policy). Abstract: The protection of geographical indications is now an important feature of trade agreements. In this paper, we examine whether geographical indications are valued by foreign consumers and whether they have implications for trade at firm level. We use firm-product level data from French Customs and a unique dataset of firms and products concerned by Protected Designations of Origin (PDO) in the cheese and butter sector. Our estimations show that PDO varieties are perceived by consumers as varieties of higher quality than non-PDO varieties and that the prices of PDO varieties are 11.5% higher than those of non-PDO. Firms producing PDO varieties do not export higher volumes, but benefit from a better access to European markets and to countries with a similar policy about geographical indications. The inclusion of some GI varieties in trade agreements may thus constitute an opportunity for PDO producers to increase their market access.